2009
DOI: 10.1007/s00464-009-0570-8
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the unexpectedly high rate of injuries caused by NOTES gastrotomy creation

Abstract: Injuries to adjacent viscera occur more often than is reported with the traditional transgastric needle knife NOTES access technique. Gastric punctures should be made either with laparoscopic visualization or by other techniques such as the PEG approach or with noncutting devices to reduce the incidence of visceral injury associated with transgastric peritoneal entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
(28 reference statements)
2
18
0
1
Order By: Relevance
“…Findings have shown that performing blind TG NOTES access can result in catastrophic complications [31]. One study reported a complication rate of 15.5% for gastrotomy creation with a needleknife and balloon dilation, concluding that gastric punctures should be made with laparoscopic visualization or with a percutaneous endoscopic gastrotomy (PEG)-like approach using noncutting devices [35]. The use of EUS [31,32] and the application of hydroperitoneum [36] have been evaluated in terms of reducing the risk of access-related complications.…”
Section: Discussionmentioning
confidence: 98%
“…Findings have shown that performing blind TG NOTES access can result in catastrophic complications [31]. One study reported a complication rate of 15.5% for gastrotomy creation with a needleknife and balloon dilation, concluding that gastric punctures should be made with laparoscopic visualization or with a percutaneous endoscopic gastrotomy (PEG)-like approach using noncutting devices [35]. The use of EUS [31,32] and the application of hydroperitoneum [36] have been evaluated in terms of reducing the risk of access-related complications.…”
Section: Discussionmentioning
confidence: 98%
“…Palpation of the anterior abdominal wall is not exact, and proves to be ineffective if the access site is low in the pelvis. In addition, needleknife cautery followed by guidewire placement or balloon dilation may be prone to accidental injury of adjacent organs, as demonstrated in transrectal and transgastric NOTES studies [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the transtracheal approaches have the advantage of enabling the surgeon to approach the target lesion head-on without the need for retroflexion, which is needed in the transesophageal approach using a gastroscope [16,17,18,19,20]. In the present study, we explored the thoracic cavity using both low and high tracheal incision methods.…”
Section: Discussionmentioning
confidence: 99%
“…One concern with the NOTES approach to the peritoneal or thoracic cavity is the risk of injuring a vital organ during wound creation [16,20]. To minimize the risk of mediastinal and lung injury, we marked the custom-designed metallic knife and tube before use, and ensured that the puncture entry of this knife did not exceed a predetermined safe length (approx.…”
Section: Discussionmentioning
confidence: 99%